Economic Empowerment of the Third Gender in India: Pathways to Inclusion and Challenges of Exclusion (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The third gender in India, encompassing transgender and non-binary individuals, has long faced economic exclusion despite recent legal recognition including the Supreme Court’s NALSA judgment (2014) and the Transgender Persons (Protection of Rights) Act (2019). However, the gap between legal provisions and economic realities remains wide, and this gap leads to discrimination such as limited access to education, health inequities, lack of financial inclusion, exclusion from formal employment, and workplace discrimination, which contribute to economic marginalization. Drawing on recent literature, this article examines both the current state of economic inclusions and exclusions faced by the third gender in accessing economic opportunities in the country. Finally, the article offers recommendations for creating a more inclusive economic environment by promoting affirmative action, skill development, and social sensitization.